Determination of natamycin (food additive in cheese production) by liquid chromatography-electrospray tandem mass spectrometry. (September 2019) - Radicevic, T; Jankovic, S; Stefanovic, S; Nikolic, D; Djinovic-Stojanovic, J; Spiric, D; Tankovic, S
Abstract: Natamycin is a polyene macrolide antifungal agent produced by aerobic fermentation of Streptomyces natalensis that prevents fungal growth on cheese surface. Commission Regulation EU 1129/2011 establishes a Union list of food additives and the use of natamycin (E235) in production of hard, semi-hard and semi-soft cheese, and lays down maximum residue limit (MRL) of 1mg/dm 2 surface. It also stipulates that natamycin is not to be present at a depth of 5mm and deeper. The aim of this study was to present the analytical method for determination of natamycin in cheese by reverse phase liquid chromatography-electrospray tandem mass spectrometry. Method validation was performed according to Commission Decision 2002/657/EC. The method is linear in the concentration ranges of 0-5 mg/dm 2, with the limit of detection (LoD) of 0.13 mg/dm 2 . The performance of the method was successfully verified by participating in a proficiency study.